2001
DOI: 10.1136/gut.48.4.526
|View full text |Cite
|
Sign up to set email alerts
|

The risk of colorectal cancer in ulcerative colitis: a meta-analysis

Abstract: Background and aims-Controversy surrounds the risk of colorectal cancer (CRC) in ulcerative colitis (UC). Many studies have investigated this risk and reported widely varying rates. Methods-A literature search using Medline with the explosion of references identified 194 studies. Of these, 116 met our inclusion criteria from which the number of patients and cancers detected could be extracted. Overall pooled estimates, with 95% confidence intervals (CI), of cancer prevalence and incidence were obtained using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

39
1,706
18
88

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 2,560 publications
(1,891 citation statements)
references
References 149 publications
39
1,706
18
88
Order By: Relevance
“…At the same time, deficiency of IL-10, an anti-inflammatory cytokine, seems to contribute to persistent intestinal inflammation (Li and He 2004;Shih and Targan 2008). Clinical reports have well document an increased risk of intestinal cancer in UC and CD patients (Askling et al 2001;Eaden et al 2001;Jess et al 2005). However, it is still unclear if any relationship exists between pro-inflammatory cytokine and IL-10 expression in IBD and the development of intestinal neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, deficiency of IL-10, an anti-inflammatory cytokine, seems to contribute to persistent intestinal inflammation (Li and He 2004;Shih and Targan 2008). Clinical reports have well document an increased risk of intestinal cancer in UC and CD patients (Askling et al 2001;Eaden et al 2001;Jess et al 2005). However, it is still unclear if any relationship exists between pro-inflammatory cytokine and IL-10 expression in IBD and the development of intestinal neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with UC are at an increased risk for the development of colorectal cancer (CRC) and the incidence worldwide varies. In the USA, the incidence is approximately 4/1,000 pyd and the overall prevalence in any UC patients is about 3.5% [1,2]. Excess mortality and morbidity in the setting of IBD is due to increased incidence of CRC [2].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike FAP and HNPCC [and sporadic CRC (SCRC)], the risk of CRC is primarily related to logstanding chronic inflammation [3]. The risk of CRC increases with increased duration and extent of UC [1,2,4]. Eaden et al [1] in a metaanalysis of 116 studies observed that the incidence of CRC based on cumulative probabilities is 2% at 10 years, 8% at 20 years, and 18% at 30 years irrespective of disease extent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory bowel disease (IBD) is associated with an increased risk of developing colorectal cancer (CRC) associated with the duration and extent of the disease [1]. Unlike sporadic CRC, CRC in IBD patients is often difficult to detect, due to the presence of ill-defined margins and often atypical gross and endoscopic appearances [2].…”
mentioning
confidence: 99%